Preparation and characterization of Arctium lappa L. polysaccharide-Zn(II) complex and evaluation of its immune activity - Yang Liu; Wanbing Pan; Lingyu Li; Jianquan Gong; Hongjing Dong; Bin Zhang; Jiahao Lin; Zhenjia Zheng (Food Chemistry Advances)
A novel Arctium lappa L. polysaccharide zinc (ALP-Zn) complex was synthesized with success. The structural characteristics, stability, and in vitro digestive properties of ALP-Zn were studied. Moreover, the immunoreactivity of ALP-Zn on murine bone marrow-derived dendritic cells (BMDCs) was investigated by examining surface molecule expression, cytokine production and endocytosis. The results showed that the weight-average molecular weight (Mw) of ALP-Zn was 60,268 Da. ALP-Zn mainly consisted of fructose, arabinose, galactose, and glucose in a mass ratio of 50.74:27.94:12.49:7.26. Zn-O characteristic peak was identified by fourier transform infrared spectroscopy at 433.42 cm−1, indicating that zinc was successfully complexed with ALP. The stability and in vitro digestive properties suggested that ALP-Zn had good stability and biological acceptability. Furthermore, ALP and ALP-Zn demonstrated excellent immunological effects on dendritic cells (DCs). After being treated with ALP and ALP-Zn, CD80 and CD86 expression on the surface of DCs were increased and DCs maturation was induced. Moreover, ALP and ALP-Zn also significantly reduced DC endocytosis and increased cytokine (IFN-γ, TNF-α, IL-1β and IL-6). As a consequence, ALP-Zn complex could be as a potential zinc supplement with immune properties.